2019
DOI: 10.1137/18m1205844
|View full text |Cite
|
Sign up to set email alerts
|

A Model Reduction Method for Multiscale Elliptic Pdes with Random Coefficients Using an Optimization Approach

Abstract: In this paper, we propose a model reduction method for solving multiscale elliptic PDEs with random coefficients in the multiquery setting using an optimization approach. The optimization approach enables us to construct a set of localized multiscale data-driven stochastic basis functions that give optimal approximation property of the solution operator. Our method consists of the offline and online stages. In the offline stage, we construct the localized multiscale data-driven stochastic basis functions by so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…that optimally approximates the input solution snapshots. Given any integer m, the POD basis functions minimize the following error 20) subject to the constraints that…”
Section: Construction Of Multiscale Reduced Basis Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…that optimally approximates the input solution snapshots. Given any integer m, the POD basis functions minimize the following error 20) subject to the constraints that…”
Section: Construction Of Multiscale Reduced Basis Functionsmentioning
confidence: 99%
“…Therefore, one can develop certain sparsity or data-driven basis functions to solve the SPDEs and RPDEs efficiently. In [7][8][9]20,39,40], Hou et al explored the Karhunen-Loève expansion of the stochastic solution, and constructed problem-dependent stochastic basis functions to solve these SPDEs and RPDEs. In [11,26], the compressive sensing technique is employed to identify a sparse representation of the solution in the stochastic direction.…”
Section: Introductionmentioning
confidence: 99%
“…The functions ϕ i (x) are called measurement functions, which are chosen as the characteristic functions on each coarse element in [24,36] and piecewise linear basis functions in [31]. In [29,22], it is found that the usage of FEM nodal basis functions reduces the approximation error and thus the same setting is adopted in the current work.…”
Section: Construction Of Multiscale Basis Functionsmentioning
confidence: 99%
“…[24] extend these works such that localized basis functions can also be constructed for higher-order strongly elliptic operators. Recently, Hou, Ma, and Zhang propose to build localized multiscale stochastic basis to solve elliptic problems with multiscale and random coefficients [22].…”
Section: Introductionmentioning
confidence: 99%
“…For linear problems, many multiscale methods have been developed. These include homogenization-based approaches [5,6], multiscale finite element methods [5,7,8], generalized multiscale finite element methods (GMsFEM) [9,10], constraint energy minimizing GMsFEM (CEM-GMsFEM) [11,12], nonlocal multi-continua (NLMC) approaches [13], metric-based upscaling [14], the heterogeneous multiscale method [15], localized orthogonal decomposition (LOD) [16], equation-free approaches [17,18], multiscale stochastic approaches [19][20][21] and the hierarchical multiscale method [22]. For high-contrast problems, approaches such as GMsFEM and NLMC have been developed.…”
Section: Introductionmentioning
confidence: 99%